Food Security Foresight: some reflections - Haniotis, Tassos (2013)
"Partnering for Impact: IFPRI-European Research Collaboration for Improved Food and Nutrition Security" presentation by Tassos Haniotis, Director, Economic Analysis, Perspectives and Evaluations DG Agriculture and Rural Development European Commission, on 25 November 2013 in Brussels, Belgium.